ANALYSIS OF FACTORS OF REGIONAL TOURISM ON THE EXAMPLE OF KHANTY-MANSI AUTONOMOUS OKRUG - Kocheryan , Maxim; Davydova , Elena; Fagina , Stanislava; Shuraleva, Natalia (Revista Inclusiones, 2020)
The purpose of the article is to analyze the factors of development of regional tourism on the example of the Khanty-Mansyisk Autonomous District - Yugra (KhMAD-Yugra). The problem of tourism development in the regions of the Russian Federation is caused by the need to achieve the goals of economic development. Tourism industry allows to increase employment, replenish budgets and attract investors. At the same time, modern research tools are needed to take into account the factors of regional tourism development. As a research method, the article uses a survey of tourists who visited the KhMAD-Yugra in 2018.